2006
DOI: 10.28945/150
|View full text |Cite
|
Sign up to set email alerts
|

Applying Chunking Theory in Organizational Password Guidelines

Abstract: This research evaluates the human impact that password authentication issues have on the security of information systems within organizations. This research resulted in the creation of password guidelines for authentication with passwords based on Miller's (1956) and Cowan's (2001) chunking theory research and a model for predicting the vulnerability that a particular set of conditions have on the likelihood of error in an information system. The findings indicate that human error associated with password auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Yan and coworkers (2004) recommended the use of mnemonic phrases, where the first letters of each word in a phrase are used as a password. Carstens, Malone, and Bell (2006) suggested using passwords consisting of meaningful chunks to improve password recall. Another type of password, the graphical password, is gaining popularity due to people's superior memory for pictures over texts (Dhamija and Perrig 2000).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Yan and coworkers (2004) recommended the use of mnemonic phrases, where the first letters of each word in a phrase are used as a password. Carstens, Malone, and Bell (2006) suggested using passwords consisting of meaningful chunks to improve password recall. Another type of password, the graphical password, is gaining popularity due to people's superior memory for pictures over texts (Dhamija and Perrig 2000).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Some of these studies are small and focus on targeted populations, such as undergraduates [9,41,54]. Others are larger online studies with a more diverse population [30,51].…”
Section: Password Corporamentioning
confidence: 99%
“…Others are larger online studies with a more diverse population [30,51]. In some cases, users are asked to create passwords for a low-value account associated with the study [9,31].…”
Section: Password Corporamentioning
confidence: 99%
“…They found that using two, three, and even four chunks of information improved memory for passwords and reduced the need for participants to refer to a written password. Although there was no statistically significant differ ence between the chunking conditions, Carstens et al (2006) found that using personally meaningful chunks of information in passwords improved memory compared to that of a sevencharacter password with no meaningful information incor porated in it. Brown et al (2004) found that half of all password constructions in their study consisted of proper names and birthdays with twothirds of passwords containing information about the self or personal elements, which makes it reasonable to suggest that these personally meaningful chunks do indeed aid memory.…”
Section: Effects Of Password Type and Memory Techniques On User Passwmentioning
confidence: 62%
“…Despite this, the usefulness of chunking in aiding memory is certainly still worth consideration today as pointed out by Carstens, Malone, and McCauleyBell (2006), who found chunking mean ingful information into passwords to be beneficial. In their study, Carstens et al (2006) explored the use of meaningful chunks of information and different password lengths. They found that using two, three, and even four chunks of information improved memory for passwords and reduced the need for participants to refer to a written password.…”
Section: Effects Of Password Type and Memory Techniques On User Passwmentioning
confidence: 99%